Data visualization: foundations, techniques, and applications - Hege, Hans Christian (2019)
The idea that there is no precedence for the amount of data that is being generated today, and that the need to explore and analyze this vast volumes of data has become an increasingly difficult task that could benefit from using Data visualization is presented. It is pointed that the goals of data visualization are data-driven and depend largely on the type of application, but the final objective is to convey to people information that is hidden in large volumes of data. Finally, the visualization pipeline is presented to review aspects of visualization methodology and visualization tool design, to conclude that the true potential of visualization emerge from the interaction of the user with the visualization model. The paper concludes establishing that the current processes of digital transformation will increase the need for visual analytics tools.